1999
DOI: 10.1097/00005392-199907000-00114
|View full text |Cite
|
Sign up to set email alerts
|

Activation for CNS Circuits Producing a Neurogenic Cystitis: Evidence for Centrally Induced Peripheral Inflammation

Abstract: We present a model of neurogenic cystitis induced by viral infection of specific neuronal circuits of the rat CNS. Retrograde infection by pseudorabies virus (PRV) of neuronal populations neighboring those that innervate the bladder consistently led to a localized immune response in the CNS and bladder inflammation. Infection of bladder circuits themselves or of circuits distant from these rarely produced cystitis. Absence of virus in bladder and urine ruled out an infectious cystitis. Total denervation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…Similarly, at lower intravesical pressures (10 -20 mmHg), the TNBSinduced sensitization of bladder afferents (as manifested by lowered sensory thresholds) was ameliorated following denervation as were changes in basal afferent activity. Although pelvic organ denervation was not performed in our previous studies of pelvic organ cross-sensitization (34), neurogenic cystitis induced in the central nervous system by the pseudorabies virus was similarly preventable by bladder denervation, again implicating neural pathways (22).…”
Section: Discussionmentioning
confidence: 79%
“…Similarly, at lower intravesical pressures (10 -20 mmHg), the TNBSinduced sensitization of bladder afferents (as manifested by lowered sensory thresholds) was ameliorated following denervation as were changes in basal afferent activity. Although pelvic organ denervation was not performed in our previous studies of pelvic organ cross-sensitization (34), neurogenic cystitis induced in the central nervous system by the pseudorabies virus was similarly preventable by bladder denervation, again implicating neural pathways (22).…”
Section: Discussionmentioning
confidence: 79%
“…For example, experimentally induced inflammation of the colon or uterus produces inflammation not only in the intentionally targeted organ but also in the bladder and the skin and animals with endometriosis have reduced bladder capacity, vaginal hyperalgesia, and increased visceral pain (28)(29)(30)(31)(32). This process requires intact CNS connections and is mediated by neurogenic inflammation; visceral and somatic pathology can be induced by inflammatory CNS lesions alone, and both referred pain and pathology can be prevented by surgically interrupting the neural connections (26,29,(30)(31)(32)(33).…”
Section: Coexistence Of Other Pain Syndromementioning
confidence: 99%
“…The phenomenon of convergence explains the higher incidence of other pelvic pain syndromes in women with vulvar dysesthesia, such as high-tone pelvic floor dysfunction, irritable bowel syndrome, and interstitial cystitis (33)(34)(35)(36). Pelvic floor tone is normal in asymptomatic women, but is increased in 10% to 100% of women with vulvar pain (15,(35)(36)(37)(38)(39).…”
Section: Coexistence Of Other Pain Syndromementioning
confidence: 99%
“…In fact, it has been demonstrated that infection of the central nervous system can produce neurogenic inflammation in the bladder via activation of central bladder circuits. 19 These effects were prevented by total denervation of the bladder or selective C-fiber deafferentation without affecting the central nervous system. 19 NGF is released after inflammatory damage and contributes to the swift modification of the pain and micturition threshold, leading to hyperalgesia and DO.…”
Section: Discussionmentioning
confidence: 99%